UPAYA MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SIFAT-SIFAT BANGUN DATAR MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE STAD - Mayasari, Dian (Jurnal Jaringan Penelitian Pengembangan Penerapan Inovasi Pendidikan (Jarlitbang), 2024)
This study aims to improve motivation and learning outcomes. The properties of flat shapes. This research was conducted at SD Negeri 3 Tempursari class VI for the 2022/2023 school year. The data in this study were obtained from the results of interviews, test results, field notes and observations. This research was conducted in two cycles. The results of the study of the learning process in the second cycle using the cooperative learning model type STAD. The average condition of students' motivation in the second cycle increased to 81.81% with a very high predicate and 18.19% with high criteria. Classical student completeness increased in cycle II, namely 10 students completed or 90.90% and 1 student did not complete. The increase in the percentage of student learning completeness from pre-cycle to cycle II was 62.74%. Based on the results of the above research, it can be concluded that the learning process using the STAD type cooperative learning model to increase motivation and learning outcomes The properties of flat shapes in grade VI semester 1 SD Negeri 3 Tempursari students in the 2022/2023 school year are more effective and increase and run smoothly in accordance with the RPP that has been prepared.